2021
DOI: 10.1101/2021.07.29.454288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of morphological diversification in the Ramphastoidea reveal the dramatic divergence of toucans from a conserved morphotype

Abstract: Morphological traits offer insights into an organism s ecological niche, species interactions, and patterns of community organisation. Pantropical lineages - animals and plants distributed across the three tropical continental regions of Asia, Africa, and America - provide a way to test how different environments and communities influence morphological diversification. Here, we examined a monophyletic group of frugivorous birds, the barbets and toucans (Ramphastoidea), which diversified independently on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The six species missing from our scan dataset are members of clades and morphological groups that were well-represented in our dataset, and are also thus unlikely to alter the patterns we observed. Drivers and functional consequences of bill shape diversification As mentioned above, previous studies have shown evidence of changes in the size of barbets without much change in body proportions (36). Here, we demonstrated that changes in size exert an influence on bill shape, with a significant effect of allometry after correcting for phylogenetic non-independence.…”
Section: The Accumulation Of Bill Shape Diversity In Asian and Africa...supporting
confidence: 72%
See 4 more Smart Citations
“…The six species missing from our scan dataset are members of clades and morphological groups that were well-represented in our dataset, and are also thus unlikely to alter the patterns we observed. Drivers and functional consequences of bill shape diversification As mentioned above, previous studies have shown evidence of changes in the size of barbets without much change in body proportions (36). Here, we demonstrated that changes in size exert an influence on bill shape, with a significant effect of allometry after correcting for phylogenetic non-independence.…”
Section: The Accumulation Of Bill Shape Diversity In Asian and Africa...supporting
confidence: 72%
“…Barbets across the tropics broadly represent a conserved morphotype, with very similar body proportions across species, except in the Neotropics (63), where the toucans have diverged into a different morphological space (36). This may have resulted from ecological opportunity (64, 65), and future studies will aim to separately explore the question of ecological opportunity and its influence on bill shape and cavity nesting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations